Pengaruh Servant Leadership, Budaya Organisasi dan Iklim Organisasi Terhadap Kepuasan Kerja Pegawai di Dinas Kearsipan dan Perpustakaan Daerah Kabupaten Karanganyar - Vinka Nirmala Putri; Putri Oktovita Sari (Indo Publishing, 2025)
Karanganyar Regency. The purpose of this study is to examine the influence of servant leadership, organizational culture and organizational climate on employee job satisfaction at the Archives and Regional Library Service of Karanganyar Regency. The type of data used is quantitative, with primary data sources. The population in this study amounted to 57 employees and the sample taken was 57 respondents using census sampling (saturated sampling). The research instrument has been tested for validity and reliability. Data analysis techniques include descriptive analysis, multiple linear regression analysis, t-test, F-test (smooth model test), coefficient of determination (R2) test. The results of this study indicate that servant leadership partially has a positive and significant effect on the job satisfaction of employees at the Karanganyar Regency Archives and Library Service (p-value) 0.000 < 0.05. Organizational culture has a positive and significant effect on the job satisfaction of employees at the Karanganyar Regency Archives and Library Service (p-value) 0.000 < 0.05. Organizational climate has a positive and significant effect on the job satisfaction of employees at the Karanganyar Regency Archives and Library Service (p-value) 0.000 < 0.05. The results of the coefficient of determination (R2) test indicate that the contribution of the independent variable to the dependent variable is 65.8%, with the remaining 34.2% influenced by factors outside the studied variables